A game theoretic approach for evaluating high-water consumption manufacturing strategies under endogenous government financial subsidies. (February 2023) - Li, Xiaona; Ma, Weimin; Shi, Honghua; Cheng, Zhengrong; Lei, Wenjing
Abstract: Motivated by the observed practices of the manufacturing industry and government, in this paper, the operational planning and water-saving strategies for a high-water-consumption (HWC) manufacturer are studied under endogenous government financial intervention in the form of subsidies. In particular, we formulate six multistage game models regarding the governments' investment cost reduction and purchase price discount policies and the manufacturer's self-saving and outsourcing-saving strategies. First, in addition to the price and production decisions, the threshold rules of water-saving strategy selection responding to a given subsidy are studied. Second, we explore the impacts of consumer environmental awareness (CEA) and the cost efficiency of water-saving innovations. Furthermore, the two subsidy schemes, namely, cost subsidy and price subsidy, are compared in terms of water-saving efforts, players' profits and government expenditures. We find that (1) CEA has a positive influence on the players' equilibrium solutions which are negatively impacted by cost efficiency. (2) The introduction of subsidy policies facilitates the outsourcing of water-saving services instead of self-saving, and the environmental, financial and social objectives of game players can be concurrently fulfilled by using a subsidy mechanism. (3) With respect to the self-saving mode, the price subsidy performs better at the water-saving level, which is opposite to that under the cost subsidy. (4) We also find that the manufacturer's free riding behavior under the price subsidy brings about a higher quantity of supply and more benefits while maintaining a high price, which leads to a heavier financial burden for the government. Despite the possibility of higher consumption and financial spending, the consumer subsidy still generates higher social welfare. Highlights: The operational planning and water-saving strategies for a manufacturer are studied. The threshold rules of water-saving strategies selection are derived by game models. The effects of consumer environmental concern and government subsidy are considered. The results provide useful guidance for the development of WSS supply chain.